Identifikasi Potensi Wisata Di Desa Ciputri Kecamatan Pacet Kabupaten Cianjur - Anggraini, Kurnia; Setiadi, Hafid; Manessa, Masita Dwi Mandini (Jurnal Pendidikan Geografi Undiksha, 2024)
Mapping in the field of tourism is useful for inventory and analysis of tourism potential in Ciputri Village which has potential natural resources. The purpose of this study is to identify the distribution of existing tourism objects, analyze tourism potential, analyze the dominant factors driving and inhibiting the development of tourist objects and analyze strategies for developing tourism potential in Ciputri Village. The method used is a qualitative method with descriptive analysis to identify and analyze the potential, development and management of tourism in Ciputri Village. Based on the results of the study, it is known that Ciputri Village has the potential of natural resources as a tourism attraction. Tourism potential that exists besides Saung Sarongge, Sarongge Coffee and Sarongge Valley Camping Ground are, Sarongge Valley Tea Agrotourism, Sarongge Flower Garden, Ciputri River Susur, Srarongge Sheep Farm, TNGGP Camping Ground and Sarongge Coffee Plantation under the foot of Mount Gelis. Development factor of potential attractions that have the attraction of beautiful natural panoramas, still original and cool. Making a map of tourism potential can help the community recognize the potential of their area and make the community an informant for visitors in Ciputri Village.